Początki drukowanej Biblii słowiańskiej na terenie Rusi Moskiewskiej - Kurianowicz, Małgorzata (Acta Polono-Ruthenica, 2012)
The article deals with the history of translation of the printed Bible into Church Slavic language in The Grand Duchy of Moscow. The first complete manuscript collection of Biblical books in the Church Slavic language was completed in The Grand Duchy of Moscow in 1499 under the auspices of Archbishop Genady of Novgorod (14841504). However, the first printed Bible appeared not in The Grand Duchy of Moscow but in south-west Rus Ostrog Bible (1581). The first printed Bible from The Grand Duchy of Moscow was just reprinted from Ostrog Bible in 1663. The article is the attempt to analyze reasons why the first printed Church Slavic Bible did not appear in The Grand Duchy of Moscow.